PENGEMBANGAN MEDIA LAYANAN INFORMASI STUDI LANJUT BERBASIS MULTIMEDIA FLIP E-BOOK UNTUK SISWA SMA - Lorantina Kartika (LP2M IAI Al Khairat Pamekasan, 2020)
Abstract:The research purposes is to result of media-based information service further studies flip multimedia e-book for high school students which acceptable theoretically and practices that can be seen in terms of usability, accuracy, attractiveness and ease. this research adopts a draft research and development from Borg & Gall. This product development is based on the results of questionnaires and interviews with counselors and students. the result of the research are based on assessment media expert, materials expert, prospective users, and small group. of the results of the assessment it can be concluded that the flip multimedia e-book being developed fit for use and acceptable theoretical and practical. Keywords: Information service, further studies, flip e-book, high school students